Online EFL Classroom Management: Voices from Indonesian EFL Teachers - M. Ali Ghufron (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2022)
Due to the scarcity of studies on online EFL classroom management in the Indonesian context, this study attempts to explore online EFL classroom management from the viewpoints of Indonesian EFL teachers in terms of its processes, strategies, and challenges. This study employed a qualitative case study approach involving 6 EFL teachers. Within three months, data were gathered through interviews with EFL teachers, which were then evaluated in a narrative way. The findings reveal that (1) in management process, teachers must make an appointment with students, prepare the content and task for online learning, deliver materials and tasks through online media, and give feedback to students’ works directly or indirectly for their evaluation or assessment; It takes a lot of processes to complete online learning management from the preparation, implementation, and evaluation stages; (2) teachers may use different strategies in managing online EFL classrooms; however, the most important points are using clear instructions in organizing the students (e.g., in doing tasks) to minimize students’ confusion, using a balance portion in using a variety of assignment methods (individual, pair, and group), and choosing interesting learning activities to engage students; and (3) the challenges faced by Indonesian EFL teachers are, among others, developing online learning materials and tasks, building a strong online learning community, and integrating teacher-student-parent relationships in online learning. This study may have implications to several parties, such as EFL teachers, students, and parents.